1) ![3^x=y; 3^{-x}=\frac{1}{y} 3^x=y; 3^{-x}=\frac{1}{y}](https://tex.z-dn.net/?f=+3%5Ex%3Dy%3B+3%5E%7B-x%7D%3D%5Cfrac%7B1%7D%7By%7D++)
![y<1+\frac{12}{y} y<1+\frac{12}{y}](https://tex.z-dn.net/?f=+y%3C1%2B%5Cfrac%7B12%7D%7By%7D++)
0 " alt=" \frac{y^2-y-12}{y}>0 " align="absmiddle" class="latex-formula">
0 " alt=" \frac{(y+3)(y-4)}{y}>0 " align="absmiddle" class="latex-formula">
Метод декомпозиции:
0 " alt=" (3^x+3^1)(3^x-3^{log_{3}(4)})>0 " align="absmiddle" class="latex-formula">
0 " alt=" (3-1)(x-log_{3}(4))>0 " align="absmiddle" class="latex-formula">
log_{3}4 " alt=" x>log_{3}4 " align="absmiddle" class="latex-formula">
2) ![2^x=y; 4^x=y^2 2^x=y; 4^x=y^2](https://tex.z-dn.net/?f=+2%5Ex%3Dy%3B+4%5Ex%3Dy%5E2+)
![4y^2<7y+2 4y^2<7y+2](https://tex.z-dn.net/?f=+4y%5E2%3C7y%2B2+)
![4y^2-7y-2<0 4y^2-7y-2<0](https://tex.z-dn.net/?f=+4y%5E2-7y-2%3C0+)
![(y-2)(y+\frac{1}{4})<0 (y-2)(y+\frac{1}{4})<0](https://tex.z-dn.net/?f=+%28y-2%29%28y%2B%5Cfrac%7B1%7D%7B4%7D%29%3C0+)
Метод декомпозиции:
![(2^x-2^1)(2^x+1/4)<0 (2^x-2^1)(2^x+1/4)<0](https://tex.z-dn.net/?f=+%282%5Ex-2%5E1%29%282%5Ex%2B1%2F4%29%3C0+)
![(2-1)(x-1)<0 (2-1)(x-1)<0](https://tex.z-dn.net/?f=+%282-1%29%28x-1%29%3C0+)
1 " alt=" x>1 " align="absmiddle" class="latex-formula">
3) ![3^x=y; 9^x=y^2 3^x=y; 9^x=y^2](https://tex.z-dn.net/?f=+3%5Ex%3Dy%3B+9%5Ex%3Dy%5E2+)
![y^2-6y-27=0 y^2-6y-27=0](https://tex.z-dn.net/?f=+y%5E2-6y-27%3D0+)
![y_{1}<0; y_{2]=3^2 y_{1}<0; y_{2]=3^2](https://tex.z-dn.net/?f=+y_%7B1%7D%3C0%3B+y_%7B2%5D%3D3%5E2+)
![3^x=3^2 3^x=3^2](https://tex.z-dn.net/?f=+3%5Ex%3D3%5E2+)
![x=2 x=2](https://tex.z-dn.net/?f=+x%3D2+)